THE STUDENTS' PERCEPTION OF USING INSTAGRAM TOWARD VOCABULARY MASTERY - Puji Handayani; Dyah Sih Pratiwi (EXPOSE (Journal of English Education and for Specific Purpose), 2023)
The purpose of this research is to find out whether Instagram has a positive impact on English vocabulary learning. The method used in this research is a qualitative method. The results show that 75% of students’ perception agree that writing captions in Instagram could help students in vocabulary mastery, this is consistent by the data 40% of students strongly agree with statement that students want to learn English vocabulary in order to create an English caption. The researcher’s conclusion that Instagram as a media for English learning has a positive impact on students' vocabulary ability at SMK Muhammadiyah 2 Bandar Lampung.